ANALISA PENGENDALIAN BIAYA PEMBANGUNAN GEDUNG PRODI KONSTRUKSI BANGUNAN POLITEKNIK TEDC BANDUNG - Prasetyo, Denny Adi; Makhdis, M Istamiul (UPPM Politeknik TEDC Bandung, 2023)
In a construction project activity, a Cost Budget Plan (RAB) is very important to get a price that is in accordance with what you want to build, and really helps contractors not to suffer losses. In fact, what happens in the field is that the Budget Plan (RAB) is not exactly the same as the Implementation Budget Plan (RAP) and that happens in every project that is implemented. The labor coefficient obtained from the labor requirement per work volume is in fact also not evenly distributed in every region in Indonesia which is called the SNI method. The general description of the project that is used as the object of research is the Building Construction Study Program Building, Tedc Bandung Polytechnic. Where the value of this project is Rp. 1,610,144,148,000. The implementation time plan is needed as a guideline for arranging the time for carrying out work that is responsible for the late project being determined from week 1 to week 14. After all the data has been collected, data processing is carried out. Based on the Yield Value Concept method, there are several initial steps, namely determining ACWP indicators for the 1st week = Rp. 3,230,827.42 and the 14th week ACWP = Rp. 6,696,150.38, BCWP 1st week = Rp. 2,657,616.10 and the 14th week BCWP = Rp. 6,917,618.39, BCWS 1st week =. Rp. 3,543,488.14 and the 14th week BCWS = Rp. 7,360,554.41.